Effect of Adoptive Transfer or Depletion of Regulatory T Cells on Triptolide-induced Liver Injury - Wang, Xinzhi; Sun, Lixin; Zhang, Luyong; Jiang, Zhenzhou (Frontiers in Pharmacology, 2016)
Objective: The aim of this study is to clarify the role of regulatory T cell (Treg) in triptolide (TP)-induced hepatotoxicity. Methods: Female C57BL/6 mice received either adoptive transfer of Tregs or depletion of Tregs, then underwent TP administration and were sacrificed 24 h after TP administration. Liver injury was determined according to alanine transaminase (ALT) and aspartate transaminase (AST) levels in serum and histopathological change in liver tissue. Hepatic frequencies of Treg cells and the mRNA expression levels of transcription factor Forkhead box P3 and retinoid orphan nuclear receptor γt (RORγt), interleukin-10 (IL-10), suppressor of cytokine signaling (SOCS), and Notch/Notch ligand were investigated. Results: During TP-induced liver injury, hepatic Treg and IL-10 decreased, while T helper 17 cells cell-transcription factor RORγt, SOCS and Notch signaling increased, accompanied with liver inflammation. Adoptive transfer of Tregs ameliorated the severity of TP-induced liver injury, accompanied with increased levels of hepatic Treg and IL-10. Adoptive transfer of Tregs remarkably inhibited the expression of RORγt, SOCS3, Notch1, and Notch3. On the contrary, depletion of Treg cells in TP-administered mice resulted in a notable increase of RORγt, SOCS1, SOCS3, and Notch3, while the Treg and IL-10 of liver decreased. Consistent with the exacerbation of liver injury, higher serum levels of ALT and AST were detected in Treg-depleted mice. Conclusion: These results showed that adoptive transfer or depletion of Tregs attenuated or aggravated TP-induced liver injury, suggesting that Tregs could play important roles in the progression of liver injury. SOCS proteins and Notch signaling affected Tregs, which may contribute to the pathogenesis of TP-induced hepatotoxicity.